Thrombus of the Aorta and SARS-CoV-2 Infection: Cause or Trigger? - Goudot, Guillaume; Amrane, Mourad; El Ayoubi, Rida; Bel, Alain; Gendron, Nicolas; Khider, Lina; Durivage, Andréanne; Smadja, David M.; Messas, Emmanuel; Achouh, Paul; Mirault, Tristan (Frontiers in Cardiovascular Medicine, 2021)
Objective: Coronavirus disease 19 is a well-established cause of rare arterial thrombosis. Nevertheless, the exact mechanism of arterial thrombosis remains to be elucidated. We herein report the case of a large floating thrombus of the aortic arch, its surgical management and histological analysis. Case: A 65-year-old patient presented to the emergency department with a suspected stroke. He was non-smoker, but presented cardiovascular risk factors, namely hypertension, type 2 diabetes and hyperlipidaemia. A computed tomography of the aorta revealed a large floating thrombus of the aortic arch, at the base of the brachiocephalic trunk, suspected to be the etiology of stroke. Therapeutic anticoagulation was immediately started. The decision was made to perform an open aortic replacement surgery because of the symptomatic thromboembolic event with recent cerebral infarction and the potential harmfulness of the thrombus due to its size. A mobile thrombus was observed at the base of the brachiocephalic trunk by echocardiography. It was attached to a small area of the upper aortic wall and had an irregular surface. Histology revealed a platelet-rich thrombus lying on an aortic atherosclerotic plaque without pronounced inflammation. No plaque ulceration was present but endothelial cell desquamation was observed consistent with plaque erosion. Conclusion: In our case, there was a thrombus lying on an atherosclerotic plaque with intact thick fibrous cap, but associated with a plaque erosion mechanism. The thrombus formation appeared more likely to relate to a very localized endothelial injury.